DEVELOPMENT AND OPTIMIZATION OF BILAYER HYDRODYANAMICALLY BALANCED SYSTEM OF AMLODIPINE BESYLATE IMMEDIATE RELEASE AND HYDROCHLOROTHIAZIDE CONTROLLED RELEASE - Hariharan, G.; Sudhakar, M.; Vinay, Rao (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: An effervescence based hydrodynamically balanced system of bilayer tablet formulation is developed with an aim to achieve the immediate release of Amlodipine Besylate (AB) and sustained release for Hydrochlorothiazide (HCTZ). Methods: The bilayer system was developed with one layer acting as a gas generating layer (Layer 1) and the second layer acting as the sustained release layer (Layer 2). AB was incorporated in Layer 1 and was targeted to release > 85% (Q) within 15 minutes. HCTZ was incorporated in Layer 2 and was targeted to release over a period of 8 hour. Results and conclusion: Water soluble matrix polymers Methocel K4M and Methocel K15M were used in combination in the sustained release layer. The ratio of K4M and K15M was optimized to achieve the target dissolution profile. The targeted release rate was in the range of 8 to 10 %/hour. Key Words: Amlodipine besylate (AB), Hydrochlorothiazide (HCTZ), HPMC K4M, HPMC K15M, hydrodynamically balanced bilayer tablets, target dissolution profile.